(untitled) (Innovate Conferences, 2025)
This article analyzes the social and economic implications of the phenomenon of inheritance. Inheritance is the process of transferring property and rights from generation to generation, which has a significant impact on the social structure and economic stability of society. The article examines the changes in inheritance laws and practices in different periods and discusses the importance of this issue in the modern era.